The Caribbean Community, the Caribbean Single Market and Economy and the CISG: Three ways of promoting international trade in the Caribbean region - Sobion, Justin (Department of Commercial Law, 2014)
The purpose of this dissertation is to provide the reader with some insight into to the Caribbean Community (CARICOM), its Single Market and Economy and the Caribbean Court of Justice. This dissertation will then culminate by addressing the United Nations Convention on Contracts for the International Sale of Goods 1980 (CISG) and the benefits of CARICOM countries in implementing same. This dissertation is divided into 4 Chapters. Chapter 1 will introduce the reader to the history, purpose and objections of CARICOM. Chapter 2 will introduce the concept of the Caribbean Single Market and Economy (CSME) and how it works in the Caribbean model. Chapter 2 will also discuss the existing preferential trade arrangements between CARICOM and other States. Chapter 3 considers the recently inaugurated Caribbean Court Justice (CCJ) and its instrumental role as an international law tribunal in interpreting the Treaty establishing the CSME. Chapter 4 will then discuss the law governing the CARICOM contract, and the question as to whether the CARICOM nations have accepted the concept of a lex mercatoria (transnational law). Focus will then be placed on the need for CARICOM nations to implement the CISG. It is desired that this dissertation would prove to be interesting and informative not only to the CARICOM reader but also readers from other parts of the world.